Low levels of Vitamin D during pregnancy associated with gestational diabetes mellitus and low birth weight: results from the MAASTHI birth cohort - Deepa, R.; Schayck, Onno C. P. Van; Babu, Giridhara R. (Frontiers in Nutrition, 2024)
Introduction: India has a high prevalence of vitamin Vitamin D insufficiency among women of childbearing age, we aim to evaluate the potential relationship of Vitamin D Deficiency deficiency with gestational diabetes mellitus (GDM) and low birth weight (LBW) in the MAASTHI birth cohort.A prospective cohort study (n=230)involving 230 participants was conducted in public hospitals located in Urban Bengaluru, India. Healthy pregnant women attending ANC between 14 to 36 weeks of gestational age were recruited after consent. An oral glucose tolerance test (OGTT) was conducted administered between 24 to 36 weeks of pregnancy and blood samples were preserved at -80 0 C for Vitamin D analysis. at birth Ffollow up at birth was conducted to recordincluded recording the anthropometry child's birth weight of the child.We found that 178 (77.4%) of women were Vitamin D deficient, 44(19.1%) were diagnosed with GDM and 64(27.8%) were LBW children. Women in the lowest quartile of serum vitaminVitamin D levels had three times higher odds of gestational diabetesGDM than women in higher quartiles [OR = 3.01 22 (95%CI: 1.023, 810.8707), p = 0.04] after adjusting for age, parity, socioeconomic status, season and adiposity. For every one-unit increase in vitaminVitamin D levels, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) decreased by about 1518%.Further, causal mediation analysis, showed that decrease in one unit of Vitamin D is associated with a decrease of 0.015 units of FBS and 0.019 units of PPBS as it flows through the mediator variable Insulin Resistance. Vitamin D Deficient women were twice at risk of giving birth to low birth weight (LBW) infants. (OR 2.04, 95% CI 0.99, 4.19, p=0.05) Discussions: Low levels of vitaminVitamin D during pregnancy is associated with greater risk of gestational diabetes and LBW in urban Bengaluru.